Interaksi Teknologi Komputer Implikasi, Tantangan, dan Peluang dalam Masyarakat - Martyani, Eka; Ikke Yamalia (JOURNAL VISION TECHNOLOGY (V-TECH), 2023)
ABSTRACT The dynamics of interaction between developments in computer technology and changes in society. The main focus of this journal is on the complex interrelationships between computer technology, culture, and social structures. Through an interdisciplinary approach, this article outlines the profound implications, challenges faced, and opportunities created by the spread and penetration of computer technology in people's daily lives. This study explores significant changes in the way people interact, communicate, and adapt to computer technology. Along with technological evolution, society has undergone complex social and cultural transformations. The social implications of the development of computer technology form new dynamics in communication patterns, interpersonal interactions, and cultural understanding. However, in this context, there are also ethical challenges that need to be addressed, including issues of privacy, surveillance, and social impact that are not yet fully understood. In addition to challenges, this journal also highlights the great opportunities that arise from the integration of computer technology. Innovations in areas such as education, business, arts, and political participation have been driven by these technological developments. Society faces new opportunities to create creative and responsive solutions to global problems through the use of technology. This journal provides in-depth insight into the relationship between computer technology and society. This research embraces the complexities of the interactions between the two, illustrating a more holistic understanding framework. By understanding the implications, facing challenges, and taking advantage of the opportunities presented by developments in computer technology, people can direct the use of technology towards a positive and sustainable impact in their daily lives.